Are unilateral and bilateral patellar tendinopathy distinguished by differences in anthropometry, body composition, or muscle strength in elite female basketball players?. Issue 5 (23rd September 2004) - Gaida, J E; Cook, J L; Bass, S L; Austen, S; Kiss, Z S
Abstract : Background: Overuse injury to the patellar tendon (patellar tendinopathy) is a major reason for interrupted training and competition for elite athletes. In both sexes, the prevalence of unilateral and bilateral tendinopathy has been shown to differ. It has been proposed that bilateral pathology may have a different aetiology from unilateral pathology. Investigation of risk factors that may be unique to unilateral and bilateral patellar tendinopathy in female athletes may reveal insights into the aetiology of this condition. Objectives: To examine whether anthropometry, body composition, or muscle strength distinguished elite female basketball players with unilateral or bilateral patellar tendinopathy. Methods: Body composition, anthropometry, and muscle strength were compared in elite female basketball players with unilateral (n  =  8), bilateral (n  =  7), or no (n  =  24) patellar tendinopathy. Body composition was analysed using a dual energy x ray absorptiometer. Anthropometric measures were assessed using standard techniques. Knee extensor strength was measured at 180°/s using an isokinetic dynamometer. z scores were calculated for the unilateral and bilateral groups (using the no tendinopathy group as controls). z scores were tested against zero. Results: The tibia length to stature ratio was approximately 1.3 (1.3) SDs above zero in both the affected and non-affected legs in the unilateral group (p<0.05). The waist to hip ratio was 0.66 (0.78) SD above zero in the unilateral group (p<0.05). In the unilateral group, leg lean to total lean ratio was 0.42 (0.55) SD above zero (p<0.07), the trunk lean to total lean ratio was 0.63 (0.68) SD below zero (p<0.05), and leg fat relative to total fat was 0.47 (0.65) SD below zero (p<0.09). In the unilateral group, the leg with pathology was 0.78 (1.03) SD weaker during eccentric contractions (p<0.07). Conclusions: Unilateral patellar tendinopathy has identifiable risk factors whereas bilateral patellar tendinopathy may not. This suggests that the aetiology of these conditions may be different. However, interpretation must respect the limitation of small subject numbers.